Kebahagiaan perspektif Bertrand Russell dan Al-Farabi: Implikasinya terhadap Masyarakat Modern - Siska Maryana; Hery Noer Aly; Japarudin Japarudin; M. Nasron; Ashadi Cahyadi; Moch Iqbal (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2026)
Abstract: Happiness is a fundamental goal and ultimately the final objective for every individual navigating life. However, in the modern era, achieving happiness is often hindered, despite being surrounded by various conveniences and material abundance, such conditions do not guarantee true happiness. This article examines the meaning of happiness from the perspectives of Bertrand Russell and Al-Farabi views that align with the needs of contemporary society and explores the implications of their thought. The study employs a literature-based research methodology, utilizing descriptive-analytical and hermeneutic-reflective approaches. For Bertrand Russell, happiness is a process of conquest balancing emotions, broadening interests, and liberating oneself from the ego rather than something that arises spontaneously, it is the result of active struggle and effort. For Al-Farabi, happiness stems from the struggle to develop human potential, cultivate the self, and align one's will with a higher, spiritual will; it originates in the perfection of the soul and places God as the ultimate pinnacle of achievement. In the context of modern society, Bertrand Russell’s thought represents a harmonious horizontal relationship characterized by social concern and active interaction with others, while Al-Farabi complements this with a sublime vertical relationship achieved through the perfection of intellect and spirit to attain true happiness.Keywords: Happiness, Bertrand Russell, Al-Farabi, modern society.Abstrak: Kebahagiaan merupakan salah satu tujuan dan selalu menjadi tujuan akhir yang ingin dicapai oleh setiap individu yang menjalani kehidupan ini. Namun, kebahagiaan di era modern seringkali terhambat meskipun dikelilingi oleh berbagai macam kemudahan dan limpahan materi, tetap tidak menjamin seseorang akan mendapatkan kebahagiaan yang sesungguhnya. Aartikel ini membahas makna kebahagiaan perspektif Bertrand Russell dan Al-Farabi yang selaras dengan apa yang sedang dibutuhkan masyarakat modern saat ini untuk memperoleh kebahagiaan dan implikasi dari pemikirannya. artikel ini menggunakan metode penelitian studi pustaka dengan pendekatan deskriptif-analitis dan hermeneutis-reflektif. Kebahagiaan bagi Bertrand Russell adalah proses penaklukan dimana seseorang menyeimbangkan emosi, memperluas minat, dan membebaskan diri dari egonya sendiri serta bukanlah sesuatu yang datang dengan sendirinya, melainkan hasil dari sebuah perjuangan dan usaha aktif. Kebahagiaan bagi Al-Farabi adalah hasil dari perjuangan dan usaha seseorang dalam mengembangkan potensi diri manusia, memperbaiki diri, dan menyelaraskan kehendak diri sendiri dengan kehendak yang lebih tinggi, bersifat spiritual, bersumber dari kesempurnaan jiwa dan menempatkan Tuhan sebagai puncak pencapaian. Dalam masyarakat modern, pemikiran Bertrand Russell mewakili hubungan horizontal yang harmonis melalui kepedulian sosial dan interaksi aktif dengan sesame, sementara Al-Farabi melengkapinya dengan hubungan vertikal yang luhur melalui penyempurnaan akal dan spiritual demi mencapai kebahagiaan sejatiKata kunci: Kebahagiaan, Bertrand Russell, Al-Farabi, masyarakat modern.